Effect of Humic Acid and Molybdate on Phosphate Adsorption in Typic Hapludult of Cigudeg, Bogor - Heri Wibowo; Benito Heru Purwanto; Supriyanto Notohadisuwarno (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2017)
Humic acids containing carboxyl and hydroxyl groups that have the ability to cover the P adsorption site in Typic Hapludults. Molybdate has similarity behaviour with phosphate in theacid soils. Research aim was to study the effects of molybdate and humic acid to the kinetics of phosphate adsorption in Typic Hapludults of Cigudeg, Bogor. Important of kinetics is to get accuration of materials transport, to control influence on anion mobility, that the assessment is needed for the efficient application of Mo and P. Aplication humic acid and molybdate as competitor anion of phosphate was conducted with combination of humic acid and Mo concentration as double anions. Many models describe the kinetics for the adsorption of phosphate by soils i.e. zero order, first order, second order, and Elovich. As ststistically, there was not interaction of humic acid and molybdate on P adsorption. Application of humic acid with rate of 100 mg.L-1 was not effective decrease P adsorption in Typic Hapludults. It was due to the pH of the adsorption system that get near to its pKa of carboxyl gruop about 5. Meanwhile aplication 2 and 5 mmol.L-1 of molybdate significantly decrease of P adsorption. The second order kinetics models apropriate to the adsorptionof P in the Typic Hapludults of Cigudeg, with determination coefficients value (R2) of 0.999-1 and standard error value (SE) of 0.001–0.011.The results suggest that the molybdate as competitor anion affected the kinetics for the adsorption of phosphate due to the charge of molybdate.